Shoot competition, root competition and reproductive allocation in Chenopodium acuminatum. (1st September 2014) - Wang, Ping; Weiner, Jacob; Cahill, James F.; Zhou, Dao Wei; Bian, Hong Feng; Song, Yan Tao; Sheng, Lian Xi; Callaway, Ray
Summary Root and shoot competition affect plant growth in different ways, but their effects on reproductive allocation have not been investigated. If root and shoot competition affect reproductive output in a population differently, this will influence the evolution of plant populations growing under various competitive regimes. We conducted a field experiment to investigate the effects of root, shoot and full competition from naturally occurring surrounding vegetation on growth and reproduction of an annual plant, Chenopodium acuminatum, under low and high soil fertility. Root competition was eliminated by inserting a PVC pipe vertically into the soil around target individuals, and shoot competition was removed by installing inverted wire cones above‐ground. Plants were measured after 11 weeks of growth. The relationships between reproductive (R) and vegetative (V) biomass among treatments were compared. Without fertilizer, the competitive response of target plants to root competition was greater than that to shoot competition, while in the fertilized treatment, the opposite was the case. Fertilization increased target plant size under no or root competition, but did not affect mean plant size for individuals experiencing shoot or full competition. Variation in size among target plants was highest under shoot competition at high fertility. The slope of log R–log V relationship under fertilized conditions was significantly higher than without fertilizer addition. The slope was higher under shoot and full competition than under root or no competition at both fertility levels. There were many more small individuals when competition was for light than for soil resources. These small individuals developed more slowly and had fewer flowering branches and lower reproductive allocation at harvest than large individuals. Synthesis. Our results demonstrated that shoot competition affects the observed pattern of reproductive allometry among individuals in the field, and this has implications for the fitness of competing plants. The steeper log R–log V slope of populations competing above‐ground may intensify the role of directional selection under light competition, making the effects of shoot competition more important than those of root competition for the evolution of weeds in fertile environments.